Decision Analysis of Alternative River Debris to Landfill Transportation Systems in Jakarta - Sari, Mega Mutiara; Inoue, Takanobu; Harryes, Regil Kentaurus; Kato, Shigeru; Septiariva, Iva Yenis; Suhardono, Sapta; Notodarmojo, Suprihanto; Delu, Kevin Foggy; Suryawan, I Wayan Koko (Department of Urban and Regional Planning, Universitas Diponegoro, 2022)
River debris in Jakarta is generated in several locations by conventional transportation. Waste transportation with traditional models is usually not time-efficient, primarily when river debris is generated every time. Transport systems that can be used for river debris include compactor systems, pre-compactor systems, and baller systems. This research uses literature study and secondary data in determining alternatives. Meanwhile, the alternative selection was carried out using the Multi-Criteria Decision Making (MCDM) method. This study uses four criteria for selecting alternatives: initial capital, type of transport container, operation and maintenance, and processing capability. The utility value of waste transportation with compaction and pre-compacting systems does not significantly have utility values of 0.722 and 0.833, respectively. At the same time, the baller system has a utility value of 0.222. This shows that the compacted system is more suitable to be applied to SPA river debris in Jakarta. The presence of a pr-compactor can also reduce the water content in-river debris.